2014
DOI: 10.1038/srep05511
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin modulates B-cell translocation gene 2 to attenuate cell proliferation of prostate carcinoma cells in both p53-dependent and p53-independent pathways

Abstract: Cisplatin is a widely used anti-cancer drug. The B-cell translocation gene 2 (BTG2) is involved in the cell cycle transition regulation. We evaluated the cisplatin effects on prostate cancer cell proliferation and the expressions of BTG2, p53, androgen receptor (AR) and prostate specific antigen (PSA) in prostate carcinoma, p53 wild-type LNCaP or p53-null PC-3, cells. Cisplatin treatments attenuated cell prostate cancer cell growth through inducing Go/G1 cell cycle arrest in lower concentration and apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
6
35
0
Order By: Relevance
“…Taken together, our results indicated that BTG2 was stimulated by p53 in human bladder cancer cells. These results are consistent with our previous studies in the prostate carcinoma cells [18,27]. Besides p53, several reports has indicated that JNK, ERK, p38, NFκB, WNT/β-catenin, AKt/sp1/ NOx4, and Src/FAK pathways also modulate BTG2 expressions in different cancer cells [28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, our results indicated that BTG2 was stimulated by p53 in human bladder cancer cells. These results are consistent with our previous studies in the prostate carcinoma cells [18,27]. Besides p53, several reports has indicated that JNK, ERK, p38, NFκB, WNT/β-catenin, AKt/sp1/ NOx4, and Src/FAK pathways also modulate BTG2 expressions in different cancer cells [28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Equal quantities of cell extract were resolved in 10% SDS‐polyacrylamide gel and then transferred electrophoretically to a Hybond‐P PVDF membrane at 100 volts for 2 h. The membrane was first blocked with 10% skim milk (Sigma‐Aldrich) in TBS‐T, and then probed using antisera against BTG2 , AKT (C67E7, Cell Signaling), pAKT (Ser473, Cell Signaling), GSK3 β (12456; Cell signaling), Phospho‐GSK3 β (5558; Cell signaling), mTOR (2983; Cell signaling), Phospho‐mTOR (2971; Cell signaling), p70S6K (9202; Cell signaling), Phospho‐p70S6K (9234; Cell signaling), or β ‐actin antiserum (SC‐1616, Santa Cruz Biotechnology). Proteins were visualized using the Western Lightning Chemiluminescence Reagent Plus detection system (PerkinElmer, Inc., Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The exact contribution from these two mechanisms to the final outcome of enhancement of efficacy remains to be clarified. Nevertheless the implication of cisplatin-induced AR decrease is wide particularly for prostate cancer as AR has been a critical factor for cancer progression [27]. Interestingly, an early report indicated that miR-34a could serve as a ULBP2 repressor in tumors [28], which might imply miR-34a plays an opposite role in such a circumstance.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell translocation gene 2 (BTG2) acts as a tumor suppressor gene for a number of cancers and it is stimulated by a p53-dependent pathway, which subsequently leads to the DNA damage. BTG2 gene belongs to an anti-proliferative family protein which has highly conserved domains of BTG-Box A (Y50–N71) and BTG-Box B (L97–E115) (11 14). It has been reported that amongst the numerous molecules that are involved in diverse anti- or pro-apoptotic signaling pathways, NF-kB is one of the key factors controlling anti-apoptotic responses.…”
Section: Introductionmentioning
confidence: 99%